Enhancing the performance of the vehicle active suspension system by an Optimal Sliding Mode Control algorithm - Duc Ngoc Nguyen; Tuan Anh Nguyen (PLoS ONE, 2022)
The suspension system determines riding comfort. This item utilizes an active suspension system to absorb vehicle vibration. A quarter-dynamics model with five state variables simulates the oscillations of a vehicle. This model incorporates the hydraulic actuator effect into linear differential equations. This is an entirely original design. In addition, the OSMC (Optimal Sliding Mode Control) algorithm is proposed for active suspension system operation control. The in-loop algorithm optimizes the controller’s parameters. According to the findings of the study, when the OSMC algorithm was implemented, the maximum and average displacement values of the sprung mass were dramatically lowered under normal oscillation conditions. If a vehicle employs only a passive suspension system or an active suspension system with a standard linear control algorithm, the wheel is fully detached from the road surface in hazardous conditions. When the OSMC algorithm is utilized to control the operation of the active suspension system, the wheel-to-road interaction is always maintained. This algorithm provides a great degree of efficiency.